Study of Symbols in Indonesian Tradition as an Effort to Improve the Covid-19 Health Messages During the Pandemic - Rina Pertiwi; Chelomitha Malindra Purnamayanti; Farhaiza Ramadhania; Yunika Tri Yulianti; Susy Katikana Sebayang (MOZAIK HUMANIORA, 2022)
The number of COVID-19 cases in Indonesia is still on the rise. The government has issued policies to suppress, anticipate, and break the chain of COVID-19 transmission, including the 5M health protocol. However, the community has not fully adhered to this appeal. Without a strong cultural basis, society may find it difficult to accept behavior change. Conflicting command norms and descriptive norms for certain types of behavior in the social context can cause discomfort. The national health message can be made stronger by incorporating symbols from traditional Indonesian fairy tales. Indonesian society has a strong oral tradition and uses stories, legends, and tales as a method of communicating norms. Incorporating symbols that are deeply rooted in culture will enhance the effectiveness of health messages and help people to quickly understand the new norms for interacting during the COVID-19 pandemic and adhere to health protocols. This study provides a list of potential symbols rooted in culture that can be used by governments, health professionals, and the general public to design strong health messages, including messages about stigma, isolation, vaccination, wearing masks, washing hands, social distancing, avoiding crowds, and reducing mobility.